Iron-silicon-aluminum magnetic powder core and preparation method and application thereof

By using a mixed insulating coating of silica and aluminum phosphate on the ferrosilicon aluminum magnetic powder core, combined with the synergistic effect of aqueous silicon sol and liquid aluminum phosphate, the inductance of the ferrosilicon aluminum magnetic powder core under high superimposed magnetic field in the prior art is solved. The problem of poor characteristics achieves the effect of taking into account both low loss and high DC superposition characteristics.

CN119446700APending Publication Date: 2025-02-14HENGDIAN GRP DMEGC MAGNETICS CO LTD +1

Patent Information

Application Number
CN202310984902.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing ferrosilicon aluminum magnetic powder core has poor inductance characteristics under high superimposed magnetic field, and the large insulating dose of low-permeability materials leads to increased loss and molding difficulty, which cannot effectively take into account the low-loss and high DC superimposed characteristics.

Method used

Silica and aluminum phosphate are used as the mixed insulating coating layer. Through the synergistic action of aqueous silicon sol and liquid aluminum phosphate, an insulating coating layer is formed in one step, reducing the eddy current loss between particles and heat treatment under high temperature environments. Avoid decomposition and crystallization of inner layer materials.

Benefits of technology

It achieves the purpose of taking into account both low loss and high DC superposition characteristics, reduces the loss of the magnetic powder core, improves the molding density and saturated flux density, and is suitable for various specifications of ferrosilicon aluminum magnetic powder matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004380775980000121
    Figure BDA0004380775980000121
  • Figure BDA0004380775980000131
    Figure BDA0004380775980000131
Patent Text Reader

Abstract

The invention provides an iron-silicon-aluminum magnetic powder core and a preparation method and application thereof. The Fe-Si-Al magnetic powder core comprises a Fe-Si-Al magnetic powder base body and a coating layer coating the surface of Fe-Si-Al magnetic powder. And the coating layer comprises silicon dioxide and aluminum phosphate. According to the Fe-Si-Al magnetic powder core provided by the invention, the silicon dioxide and the aluminum phosphate are used as the mixed insulating coating layer, so that the resistivity of the Fe-Si-Al magnetic powder core is increased, the eddy-current loss among particles is effectively reduced, meanwhile, the maximum forming density of the material is ensured, and a relatively high saturation magnetic flux density Bs is obtained, so that a high direct-current superposition characteristic is obtained; and the aim of giving consideration to low loss and high direct current superposition characteristics is fulfilled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials and relates to a sendust magnetic powder core and a preparation method and application thereof. Background Art

[0002] Sendust metal powder core has the lowest loss (100kHz, 100mT, Pcv≤260mW / cm 3 ) and is widely used in the manufacture of various electronic components, but its inductance has poor DC superposition characteristics (with the increase of superimposed DC magnetic field strength, its magnetic permeability decreases greatly). For a magnetic core with a magnetic permeability of 60u, when the magnetic field strength is 100Oe, the inductance is only 55% of its initial value; in order to enable the sendust magnetic powder core to be used in large current (high superimposed magnetic field) situations, its initial magnetic permeability is reduced to 26u or even lower, which can greatly improve its superposition characteristics. Magnetic powder core is a new type of composite soft magnetic material formed by mixing ferromagnetic metal powder with insulating agent and adhesive. Insulation coating is a key step in the preparation of metal soft magnetic composite materials. The amount of insulating agent required for low magnetic permeability 26u and 19u magnetic powder cores is three, four or even more than that of 60u materials, which causes the core loss and molding difficulty to increase exponentially, hindering the application of low magnetic permeability magnetic powder core materials.

[0003] CN102543345A discloses a method for making a FeSiAl magnetic powder material with a magnetic permeability μ=26 by using phosphate for insulation coating, and the powder is heated and roasted before adding phosphoric acid, which increases the complexity and cost of the process; however, the phosphate is easy to fall off during the pressing process and easy to decompose during the annealing process, the loss of the magnetic powder core is high, and the magnetic core density is not enough, and the inductance under a 100Oe DC superposition magnetic field is only 75%, which is not up to the industry leading level. CN111696744A discloses a process for making a high-superposition FeSiAl magnetic powder core material by using silicone-modified epoxy resin + oxidized powder to insulate and coat metal powder, which can effectively solve the molding problem and high-temperature annealing problem, but the process is relatively complicated, has more organic components, is costly, and is not environmentally friendly.

[0004] The key to improving the inductance of Sendust magnetic powder core materials under DC superposition fields is to increase the saturation flux density Bs; especially for materials with low magnetic permeability μ=19~26, the proportion of non-magnetic materials added is much higher than μ=60, which makes it difficult to achieve low material loss and high DC superposition characteristics at the same time.

[0005] CN115064331A discloses a method for coating a magnetic powder core with a silicon dioxide layer, wherein the silicon dioxide is derived from nano-SiO 2 Powder or silica sol, which converts SiO 2, or silica sol is mixed with dispersed organic resin (such as epoxy resin, polyurethane, silicone resin) solution, and the powder is mixed and coated. The powder can also be coated twice, and the coating material is water glass and silica sol solution; after drying, lubricant is added and then molded. The magnetic permeability of the magnetic core prepared by this process is above 130μ, and the DC bias is low. Therefore, the application field of this material is small, and it does not meet the requirements of low loss and high DC superposition characteristics of the material.

[0006] Therefore, how to ensure that the magnetic powder core prepared from low magnetic permeability Sendust magnetic powder has good insulation and high saturation flux density Bs, and how to achieve both low loss and high DC superposition characteristics of the magnetic powder core, is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a sendust magnetic powder core and a preparation method and use thereof. The sendust magnetic powder core provided by the present invention uses silicon dioxide and aluminum phosphate as a mixed insulating coating layer, increases the resistivity of the sendust magnetic powder core, effectively reduces the eddy current loss between particles, and at the same time ensures the maximum molding density of the material, obtains a higher saturation flux density Bs and then obtains a high DC superposition characteristic, achieving the purpose of taking both low loss and high DC superposition characteristics into consideration.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a sendust magnetic powder core, the sendust magnetic powder core comprising a sendust magnetic powder matrix and a coating layer coated on the surface of the sendust magnetic powder; the coating layer comprises silicon dioxide and aluminum phosphate.

[0010] In the coating layer of the sendust magnetic powder core provided by the present invention, aluminum phosphate may react with the matrix and inevitably generate other phosphate materials, such as iron phosphate.

[0011] The sendust magnetic powder core provided by the present invention uses silicon dioxide and aluminum phosphate as mixed insulating agents to form a coating layer on the surface of the magnetic powder. The two substances work synergistically to increase the resistivity of the sendust magnetic powder core, effectively reduce the eddy current loss between particles, and at the same time ensure the maximum molding density of the material, obtain a higher saturation flux density Bs and then obtain a high DC superposition characteristic, and achieve the purpose of taking both low loss and high DC superposition characteristics into account; and the sendust magnetic powder matrix can be applied to various specifications (such as specifications of 200 to 500 meshes and specifications below 500 meshes, and the distinction of the above specifications is well known to those skilled in the art).

[0012] In the present invention, a single silica coating layer or a single aluminum phosphate coating layer cannot achieve the coating of sendust magnetic powder with a low magnetic permeability u=26, because low magnetic permeability requires a large number of insulating layers to achieve, but a single large amount of silica or aluminum phosphate has problems such as low bonding strength and high loss; and even if it is a double-layer coating, that is, the silica and aluminum phosphate are not in the same layer, but are layered, an insulating layer with a low magnetic permeability cannot be obtained, because there is no bonding force between the silica coating and the aluminum phosphate coating.

[0013] In a second aspect, the present invention provides a method for preparing the sendust magnetic powder core as described in the first aspect, the preparation method comprising the following steps:

[0014] Sendust magnetic powder, aqueous silica sol and liquid aluminum phosphate are mixed and coated, pressed into shape, and heat treated to obtain the Sendust magnetic powder core.

[0015] The preparation method provided by the present invention adopts silica sol and liquid aluminum phosphate as mixed coating agents, and the silica sol aqueous solution provides a solvent for the aluminum phosphate, and the two coating agents act synergistically to form an insulating layer on the surface of the sendust magnetic powder after drying through a one-step insulation coating process (that is, the two coating agents are coated at the same time, rather than in steps). After the magnetic powder is formed, it is directly heat-treated in a high-temperature environment, which effectively avoids the decomposition and crystallization of the inner layer material at the high-temperature annealing temperature, thereby obtaining a sendust magnetic powder core with low loss, high superposition and high quality factor; the eddy current loss between particles is effectively reduced, and the maximum molding density of the material is guaranteed at the same time, a higher saturation flux density Bs is obtained, and then a high DC superposition characteristic is obtained, achieving the purpose of taking both low loss and high DC superposition characteristics into consideration; at the same time, the preparation method provided by the present invention has a simple process, does not need to repeat the coating process, is easy to operate, has low cost, and has high production efficiency, and the method is green and environmentally friendly, and is suitable for large-scale industrial production.

[0016] In the present invention, aqueous silica sol and liquid aluminum phosphate (aluminum dihydrogen phosphate) are directly selected as coating agents without adding additional solvents. The aqueous silica sol is used as the insulating coating raw material and also as a solvent. At the same time, in the case of multiple coating agents, the present invention only adopts a one-step coating method without multiple coatings, and can achieve the purpose of taking both low loss and high DC superposition characteristics into consideration.

[0017] In the present invention, aqueous silica sol and liquid aluminum phosphate are selected as coating agents. The synergistic effect of the two can achieve the coating of sendust magnetic powder with low magnetic permeability u=26. Because low magnetic permeability requires a large number of insulating layers to achieve, the simultaneous action of the two to form a coating layer solves the problems of low bonding strength and high loss caused by layered coating. If other coating agents are selected, such as the combination of phosphoric acid and aqueous silica sol or the combination of silicone resin and liquid aluminum phosphate, the result of obtaining low magnetic permeability powder by one-step coating cannot be obtained, and layered coating cannot solve the problems of low bonding strength and high loss at the same time.

[0018] Preferably, the mixed coating comprises:

[0019] Firstly, water-soluble silica sol and liquid aluminum phosphate are mixed to obtain a mixed liquid, and then the mixed liquid is mixed with sendust magnetic powder again.

[0020] In the present invention, water-soluble silica sol and liquid aluminum phosphate are first mixed to achieve dissolution and uniform mixing of the coating agent.

[0021] Preferably, the remixing time is 10 to 20 min, for example, 10 min, 13 min, 15 min, 18 min or 20 min.

[0022] Preferably, the added amount of the aqueous silica sol is 6.5-10% of the mass of the sendust magnetic powder, for example, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%.

[0023] Preferably, the added amount of the liquid aluminum phosphate is 5.5-9.5% of the mass of the sendust magnetic powder, for example, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9% or 9.5%.

[0024] In the present invention, the addition amount of aqueous silica sol (6.5-10%) and the addition amount of liquid aluminum phosphate (5.5-9.5%) cooperate with each other to achieve the purpose of preparing low magnetic permeability Sendust powder by one-step insulation coating. If the addition amount of either party is too large or too small, it will lead to problems of low bonding strength or high loss.

[0025] Specifically, if the amount of aqueous silica sol added is too much, exceeding 10%, it will affect the insulation effect, causing the insulation layer to become thicker and the loss to be high; while if the amount added is too little, less than 6.5%, it will result in a small amount of silica, poor effect of filling the pores of the aluminum phosphate coating layer, and low strength of the insulation layer.

[0026] If the amount of liquid aluminum phosphate added is too much, exceeding 9.5%, it will not be conducive to reducing the thickness of the insulating layer, resulting in low magnetization intensity Bs and high loss. If the amount added is too little, less than 5.5%, it will not be able to achieve the requirement of quickly reducing the magnetic permeability of the magnetic powder, resulting in a significant increase in the amount of silicon dioxide and low insulation layer strength.

[0027] Preferably, the mixed coating is followed by drying.

[0028] Preferably, the drying temperature is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C or 100°C.

[0029] Preferably, the drying time is 5 to 15 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min.

[0030] After the mixing and coating, the present invention does not need to be dried at a high temperature, and the water can be simply removed, which takes a short time and is at a low temperature.

[0031] Preferably, a reinforcing agent and a lubricant are added to the mixed and coated material.

[0032] Preferably, the powder particle size of the reinforcing agent is 1000-1500 mesh, for example, 1000 mesh, 1100 mesh, 1200 mesh, 1300 mesh, 1400 mesh or 1500 mesh.

[0033] Preferably, the added amount of the reinforcing agent is 0.15-0.5% of the mass of the Sendust magnetic powder, for example, 0.15%, 0.2%, 0.3%, 0.4% or 0.5%.

[0034] Preferably, the reinforcing agent comprises any one of kaolin, talc or silicon dioxide, or a combination of at least two thereof.

[0035] Preferably, the added amount of the lubricant is 0.3-0.4% of the mass of the Sendust magnetic powder, such as 0.3%, 0.35% or 0.4%.

[0036] Preferably, the lubricant includes any one of aluminum stearate, zinc stearate or magnesium stearate, or a combination of at least two of them.

[0037] Preferably, the pressure during the press-forming process is 1500-2500 MPa, for example, 1500 MPa, 1800 MPa, 2000 MPa, 2300 MPa or 2500 MPa.

[0038] Preferably, the atmosphere of the heat treatment is a protective atmosphere.

[0039] Preferably, the temperature of the heat treatment is 700-850°C, for example, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C, etc.

[0040] Preferably, the heat treatment time is 30 to 40 min, for example, 30 min, 33 min, 35 min, 38 min or 40 min.

[0041] As a preferred technical solution, water-soluble silica sol and liquid aluminum phosphate are first mixed to obtain a mixed liquid, and then the mixed liquid is mixed again with sendust magnetic powder for 10 to 20 minutes, dried at 80 to 100° C. for 5 to 15 minutes, and then a reinforcing agent and a lubricant are added, and the mixture is pressed under a pressure of 1500 to 2500 MPa, and heat-treated at 700 to 850° C. for 30 to 40 minutes in a protective atmosphere;

[0042] Wherein, the added amount of the aqueous silica sol is 6.5-10% of the mass of the sendust magnetic powder; the added amount of the liquid aluminum phosphate is 5.5-9.5% of the mass of the sendust magnetic powder.

[0043] It should be noted that the aqueous silica sol and liquid aluminum phosphate in the present invention are not prepared but directly purchased.

[0044] In a third aspect, the present invention further provides a use of the Sendust magnetic powder core as described in the first aspect, wherein the use includes using the Sendust magnetic powder core in an inductive device.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The Sendust magnetic powder core provided by the present invention has a mixed insulating coating layer of silicon dioxide and aluminum phosphate. The two substances work synergistically to increase the resistivity of the Sendust magnetic powder core, effectively reduce the eddy current loss between particles, and at the same time ensure the maximum molding density of the material, obtain a higher saturation flux density Bs and thus obtain a high DC superposition characteristic, achieving the purpose of taking both low loss and high DC superposition characteristics into account; and the sendust magnetic powder matrix can be applied to various specifications.

[0047] (2) The preparation method provided by the present invention adopts aqueous silica sol and liquid aluminum phosphate as mixed coating agents, which work synergistically to form an insulating layer on the surface of the sendust magnetic powder after drying through a one-step insulation coating process (i.e., two coating agents are coated at the same time, rather than in steps). After the magnetic powder is formed, it is directly heat treated in a high-temperature environment, which effectively avoids the decomposition and crystallization of the inner layer material at the high-temperature annealing temperature, thereby obtaining a sendust magnetic powder core with low loss, high superposition and high quality factor; effectively reduces the eddy current loss between particles, while ensuring the maximum molding density of the material, obtains a higher saturation flux density Bs and then obtains a high DC superposition characteristic, achieving the purpose of taking both low loss and high DC superposition characteristics into account; at the same time, the preparation method provided by the present invention has a simple process, does not require repeated coating process, is easy to operate, has low cost, and has high production efficiency. Moreover, the method is green and environmentally friendly, and is suitable for large-scale industrial production. DETAILED DESCRIPTION

[0048] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0049] Example 1

[0050] The present embodiment provides a sendust magnetic powder core, which includes a sendust magnetic powder matrix and a coating layer coated on the surface of the sendust magnetic powder; the coating layer includes silicon dioxide and aluminum phosphate.

[0051] The preparation method of the Sendust magnetic powder core is as follows:

[0052] Prepare 5 kg of Fe-Si-Al alloy magnetic powder with a particle size range of 200-500 mesh and a median diameter D50 of 25-55 μm, and prepare a portion of aqueous silica sol (molecular formula: mSiO 2 ·nH 2 O), 7% by mass is based on the mass of the iron-silicon-aluminum alloy magnetic powder, that is, 7% by mass of the iron-silicon-aluminum alloy magnetic powder); prepare a portion of liquid aluminum phosphate (molecular formula: Al(H 2 PO 4 ) 3 ) solution, accounting for 6.5% by mass (based on the mass of the Sendust magnetic powder, i.e. 6.5% by mass of the Sendust magnetic powder);

[0053] Mix the aqueous silica sol and the liquid aluminum phosphate solution and stir for 3 minutes; add the mixed coating solution to the magnetic powder, stir for 15 minutes, then introduce into a heating pot and stir-fry until dry and dispersed (the temperature of the heating pot is 80°C and the drying time is 10 minutes);

[0054] After the above insulation treatment, the magnetic powder is placed to cool to room temperature; then 0.35wt% of kaolin (1000 mesh) and 0.3wt% of zinc stearate are added and ground and mixed evenly (based on the mass of the sendust magnetic powder, i.e. 0.35% and 0.3% of the mass of the sendust magnetic powder), and then pressed into a ring (26.9mmOD×14.7mmID×11.2mmtall) under room temperature and 1700MPa pressing conditions; the pressed ring is heat treated at a maximum of 700°C for 30 minutes in a nitrogen atmosphere, and the total heating and treatment time does not exceed 150 minutes to obtain the sendust magnetic powder core.

[0055] Example 2

[0056] The present embodiment provides a sendust magnetic powder core, which includes a sendust magnetic powder matrix and a coating layer coated on the surface of the sendust magnetic powder; the coating layer includes silicon dioxide and aluminum phosphate.

[0057] The preparation method of the Sendust magnetic powder core is as follows:

[0058] Prepare 5 kg of Fe-Si-Al alloy magnetic powder with a particle size range of 200-500 mesh and a median diameter D50 of 25-55 μm, and prepare a portion of aqueous silica sol (molecular formula: mSiO 2 ·nH 2 O), 10% by mass is based on the mass of the iron-silicon-aluminum alloy magnetic powder, that is, 10% by mass of the iron-silicon-aluminum alloy magnetic powder); prepare a portion of liquid aluminum phosphate (molecular formula: Al(H 2 PO 4 ) 3 ) solution, accounting for 9.5% by mass (based on the mass of the Sendust magnetic powder, i.e. 9.5% by mass of the Sendust magnetic powder);

[0059] Mix the aqueous silica sol and the liquid aluminum phosphate solution and stir for 3 minutes; add the mixed coating solution to the magnetic powder, stir for 15 minutes, then introduce into a heating pot and stir-fry until dry and dispersed (the temperature of the heating pot is 80°C and the drying time is 10 minutes);

[0060] After the above insulation treatment, the magnetic powder is allowed to cool to room temperature; then 0.35wt% of kaolin (1000 mesh) and 0.3wt% of zinc stearate are added and ground and mixed evenly (based on the mass of the sendust magnetic powder, i.e., 0.35% and 0.3% of the mass of the sendust magnetic powder), and then pressed into a ring (26.9mmOD×14.7mmID×11.2mmtall) under room temperature and 1700MPa pressing conditions; the pressed ring is heat treated at a maximum of 850°C for 30 minutes in a nitrogen atmosphere, and the total heating and treatment time does not exceed 150 minutes to obtain the sendust magnetic powder core.

[0061] Example 3

[0062] The difference between this embodiment and embodiment 1 is that the mass proportion of the aqueous silica sol in this embodiment is 5%.

[0063] The rest of the preparation methods and parameters were the same as those in Example 1.

[0064] Example 4

[0065] The difference between this embodiment and embodiment 1 is that the mass proportion of the aqueous silica sol in this embodiment is 11%.

[0066] The rest of the preparation methods and parameters were the same as those in Example 1.

[0067] Example 5

[0068] The difference between this embodiment and embodiment 1 is that the mass proportion of liquid aluminum phosphate in this embodiment is 5%.

[0069] The rest of the preparation methods and parameters were the same as those in Example 1.

[0070] Example 6

[0071] The difference between this embodiment and embodiment 1 is that the mass proportion of liquid aluminum phosphate in this embodiment is 10%.

[0072] The rest of the preparation methods and parameters were the same as those in Example 1.

[0073] Example 7

[0074] The present embodiment provides a sendust magnetic powder core, which includes a sendust magnetic powder matrix and a coating layer coated on the surface of the sendust magnetic powder; the coating layer includes silicon dioxide and aluminum phosphate.

[0075] The preparation method of the Sendust magnetic powder core is as follows:

[0076] Prepare 5 kg of Fe-Si-Al alloy magnetic powder with a particle size range of less than 500 mesh and a median diameter D50 of 15 to 20 μm, and prepare a portion of aqueous silica sol (molecular formula: mSiO 2 ·nH 2 O), accounting for 8.5% by mass (based on the mass of the iron-silicon-aluminum alloy magnetic powder, i.e. 8.5% by mass of the iron-silicon-aluminum alloy magnetic powder); prepare a portion of liquid aluminum phosphate (molecular formula: Al(H 2 PO 4 ) 3 ) solution, accounting for 8.5% by mass (based on the mass of the Sendust magnetic powder, i.e. 8.5% by mass of the Sendust magnetic powder);

[0077] Mix the aqueous silica sol and the liquid aluminum phosphate solution and stir for 3 minutes; add the mixed coating solution to the magnetic powder, stir for 20 minutes, then introduce into a heating pot and stir-fry until dry and dispersed (the temperature of the heating pot is 90°C and the drying time is 5 minutes);

[0078] After the above insulation treatment, the magnetic powder is placed to cool to room temperature; then 0.5wt% of kaolin (1000 mesh) and 0.4wt% of zinc stearate are added and ground and mixed evenly (based on the mass of the sendust magnetic powder, i.e. 0.5% and 0.4% of the mass of the sendust magnetic powder), and then pressed into a ring (26.9mmOD×14.7mmID×11.2mmtall) under room temperature and 1800MPa pressing conditions; the pressed ring is heat treated at a maximum temperature of 750°C for 30 minutes in a nitrogen atmosphere, and the total heating and treatment time does not exceed 150 minutes to obtain the sendust magnetic powder core.

[0079] Example 8

[0080] The difference between this embodiment and embodiment 7 is that in this embodiment, the mass proportion of aqueous silica sol is 10%, and the mass proportion of liquid aluminum phosphate is 9.5%.

[0081] The rest of the preparation methods and parameters were the same as those in Example 7.

[0082] Comparative Example 1

[0083] This comparative example provides a sendust magnetic powder core, and the preparation method of the sendust magnetic powder core is as follows:

[0084] 5 kg of iron-silicon-aluminum alloy magnetic powder of the same specification as in Example 1 was selected; each time a phosphoric acid solution with a weight ratio of 0.75 wt% of the powder was added (a total of 7 times, a total phosphoric acid content of 5.25%) for passivation, and after mixing evenly, it was transferred to an airflow drying fan and dried at 120° C. for 5 min; then aluminum dihydrogen phosphate material with a weight ratio of 5.25 wt% (added in 7 batches, each time accounting for 0.75 wt%) was taken, first dissolved in deionized water of equal weight and diluted to a coating liquid, and the final treated insulating magnetic powder was obtained after stirring evenly, and then 0.6% of the powder was added to the powder silicone resin and 0.35 wt% of zinc stearate, and the mixture was ground and mixed evenly, and then pressed into a ring (26.9 mm OD×14.7 mm ID×11.2 mm tall) at 25° C. and 1700 MPa; the pressed ring was then heat treated at 700° C. in a nitrogen atmosphere for 30 minutes to obtain a metal core magnetic ring.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 1 is that in this comparative example, only aqueous silica sol is coated, and liquid aluminum phosphate is not added.

[0087] The rest of the preparation methods and parameters were the same as those in Example 1.

[0088] Comparative Example 3

[0089] The difference between this comparative example and Example 1 is that in this comparative example, only liquid aluminum phosphate is coated, and no aqueous silica sol is added.

[0090] The rest of the preparation methods and parameters were the same as those in Example 1.

[0091] Comparative Example 4

[0092] This comparative example provides a sendust magnetic powder core, and the preparation method of the sendust magnetic powder core is as follows:

[0093] 5 kg of iron-silicon-aluminum alloy magnetic powder of the same specification as in Example 2 was selected; 0.3 wt % silane coupling agent (KH550) was added to the powder weight ratio, first dissolved in 5 times the mass of ethanol, mixed evenly and then transferred to an airflow drying fan and dried at 120° C. for 5 min; then phosphoric acid liquid, 7.5 wt % by weight (added in 5 batches, 1.5 wt % each time), was first dissolved in 3 times the weight of deionized water and diluted to a coating liquid, stirred evenly and then transferred to a hot air drying fan to dry to obtain the final treated insulating magnetic powder, then 0.6 wt % of powder silicone resin and 0.3 wt % of zinc stearate were added to grind and mix evenly, and then pressed into a ring (26.9 mm OD × 14.7 mm ID × 11.2 mm tall) at room temperature and 1800 MPa; the pressed ring was then heat treated at 750° C. for 30 minutes in a nitrogen atmosphere to obtain a metal core magnetic ring.

[0094] The performance of the sendust magnetic powder cores provided in Examples 1-8 and Comparative Examples 1-4 was tested under the following test conditions: the performance test was performed using a magnetic winding wire, with 20 turns of each primary coil and secondary coil, the inductance was tested using an LCR CH3303 inductor, and then the magnetic permeability was obtained; the total loss was measured using an AC BH meter under loads of 50mT, 100mT and a frequency of 50kHz; and a DC superposition characteristic test was performed; the specific test results are shown in Table 1.

[0095] Table 1

[0096]

[0097]

[0098] From Table 1 we can see that:

[0099] It can be seen from the data results of Examples 1-2 and Examples 7-8 that the Sendust magnetic powder core structure provided by the present invention is suitable for magnetic powders of various specifications, and the preparation method is also suitable for magnetic powders of various specifications. The method is universal and achieves the purpose of taking both low loss and high DC superposition characteristics into account.

[0100] From the data results of Example 1 and Examples 3-6, it can be seen that the amount of aqueous silica sol added and the amount of liquid aluminum phosphate added in the present invention work synergistically and affect each other's density, resistivity and bonding strength of the coating layer. Too little or too much addition of any one of them will affect the balance of magnetic permeability, loss and superposition characteristics. The most likely possibility is that under the same magnetic permeability, the loss deteriorates and the superposition is insufficient.

[0101] From the data results of Examples 1-2 and Comparative Example 1, and Examples 7-8 and Comparative Example 4, it can be seen that the preparation method provided by the present invention does not require repeated coating, reduces the number of coating times, omits the preparation process, saves time and cost, and achieves the purpose of taking both low loss and high DC superposition characteristics into account.

[0102] From the data results of Example 1 and Comparative Examples 2 and 3, it can be seen that the aqueous silica sol and liquid aluminum phosphate in the present invention work synergistically, and both are indispensable. Indeed, any one of the raw materials cannot achieve the purpose of achieving both low loss and high DC superposition characteristics by one-step insulation coating.

[0103] In summary, the present invention utilizes water-soluble silica gel and liquid aluminum phosphate as main insulating coating agents, and forms an inorganic insulating layer on the surface of the sendust magnetic powder after drying through one-step coating addition. After the magnetic powder is formed, it is directly heat-treated in a high-temperature environment, which effectively avoids the decomposition and crystallization of the inner layer material at the high-temperature annealing temperature, so as to effectively protect the resistivity of the material and reduce the eddy current loss of the material; at the same time, the maximum molding density of the material is guaranteed, a higher saturation magnetic flux density Bs is obtained, and then a high DC superposition characteristic is obtained, achieving the purpose of taking both low loss and high DC superposition characteristics into account; and the preparation method has a simple process, does not require repeated coating process, is easy to operate, has low cost, and has high production efficiency, and the method is green and environmentally friendly, and is suitable for large-scale industrial production.

[0104] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0105] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0106] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0107] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A Sendust magnetic powder core, characterized in that: The Sendust magnetic powder core comprises a Sendust magnetic powder matrix and a coating layer coated on the surface of the Sendust magnetic powder; the coating layer comprises silicon dioxide and aluminum phosphate.

2. A method for preparing the Sendust magnetic powder core according to claim 1, characterized in that: The preparation method comprises the following steps: Sendust magnetic powder, aqueous silica sol and liquid aluminum phosphate are mixed and coated, pressed into shape, and heat treated to obtain the Sendust magnetic powder core.

3. The method for preparing the Sendust magnetic powder core according to claim 2, characterized in that: The mixed coating comprises: Firstly, water-soluble silica sol and liquid aluminum phosphate are mixed to obtain a mixed liquid, and then the mixed liquid is mixed again with sendust magnetic powder; Preferably, the remixing time is 10 to 20 minutes.

4. The method for preparing the Sendust magnetic powder core according to claim 2 or 3, characterized in that: The amount of the aqueous silica sol added is 6.5-10% of the mass of the sendust magnetic powder; Preferably, the added amount of the liquid aluminum phosphate is 5.5-9.5% of the mass of the sendust magnetic powder.

5. The method for preparing the Sendust magnetic powder core according to any one of claims 2 to 4, characterized in that: The mixed coating is then dried; Preferably, the drying temperature is 80-100°C; Preferably, the drying time is 5 to 15 minutes.

6. The method for preparing the Sendust magnetic powder core according to any one of claims 2 to 5, characterized in that: adding a reinforcing agent and a lubricant to the mixed and coated material; Preferably, the powder particle size of the reinforcing agent is 1000-1500 mesh; Preferably, the amount of the reinforcing agent added is 0.15-0.5% of the mass of the sendust magnetic powder; Preferably, the reinforcing agent comprises any one of kaolin, talc or silicon dioxide or a combination of at least two thereof; Preferably, the amount of the lubricant added is 0.3-0.4% of the mass of the Sendust magnetic powder; Preferably, the lubricant includes any one of aluminum stearate, zinc stearate or magnesium stearate, or a combination of at least two of them.

7. The method for preparing the Sendust magnetic powder core according to any one of claims 2 to 6, characterized in that: The pressure during the compression molding process is 1500-2500 MPa.

8. The method for preparing the Sendust magnetic powder core according to any one of claims 2 to 7, characterized in that: The atmosphere of the heat treatment is a protective atmosphere; Preferably, the temperature of the heat treatment is 700-850°C; Preferably, the heat treatment time is 30 to 40 minutes.

9. The method for preparing the Sendust magnetic powder core according to any one of claims 2 to 8, characterized in that: Firstly, water-soluble silica sol and liquid aluminum phosphate are mixed to obtain a mixed liquid, and then the mixed liquid is mixed with sendust magnetic powder again for 10 to 20 minutes, dried at 80 to 100° C. for 5 to 15 minutes, and then a reinforcing agent and a lubricant are added, and the mixture is pressed under a pressure of 1500 to 2500 MPa, and heat-treated at 700 to 850° C. for 30 to 40 minutes in a protective atmosphere; Wherein, the added amount of the aqueous silica sol is 6.5-10% of the mass of the sendust magnetic powder; the added amount of the liquid aluminum phosphate is 5.5-9.5% of the mass of the sendust magnetic powder.

10. A use of the Sendust magnetic powder core as claimed in claim 1, characterized in that: The application includes using the sendust magnetic powder core in an inductive device.

Citation Information

Patent Citations

  • Low power consumption Fe-Si-Al alloy material with magnetic conductivity mu=26 and preparation method thereof

    CN102543345A

  • Iron-silicon-aluminum soft magnetic powder core with high direct-current bias performance and preparation method of iron-silicon-aluminum soft magnetic powder core

    CN111696744A

Cited By

  • Iron-nickel metal magnetic powder core with high stable magnetic conductivity and low loss and preparation method of iron-nickel metal magnetic powder core

    CN120473278A